2016
DOI: 10.3389/fcimb.2016.00022
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogen-Occupied Vacuoles of Anaplasma phagocytophilum and Anaplasma marginale Interact with the Endoplasmic Reticulum

Abstract: The genus Anaplasma consists of tick-transmitted obligate intracellular bacteria that invade white or red blood cells to cause debilitating and potentially fatal infections. A. phagocytophilum, a human and veterinary pathogen, infects neutrophils to cause granulocytic anaplasmosis. A. marginale invades bovine erythrocytes. Evidence suggests that both species may also infect endothelial cells in vivo. In mammalian and arthropod host cells, A. phagocytophilum and A. marginale reside in host cell derived pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 67 publications
(115 reference statements)
4
48
0
Order By: Relevance
“…As reported previously for the AmV in ISE6 cells, ultrastructural evaluation (Fig. 11B) confirmed that rough endoplasmic reticulum (RER) that was devoid of ribosomes on the contact side segmentally covered the outer aspect of the AmVs (29).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…As reported previously for the AmV in ISE6 cells, ultrastructural evaluation (Fig. 11B) confirmed that rough endoplasmic reticulum (RER) that was devoid of ribosomes on the contact side segmentally covered the outer aspect of the AmVs (29).…”
Section: Resultssupporting
confidence: 86%
“…Similar to A. phagocytophilum, the AmVs engaged the ER and the Golgi apparatus early in infection and maintained association throughout the course of infection (29,38,39). The ER and the Golgi apparatus are nutrient-rich compartments of the secretory pathway and likely serve as a rich source of glycoprotein and lipids, which can be degraded to supply amino acids, fatty acids, nitrogen, carbon, and energy to auxotrophic A. marginale (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…However, less information is available on the bacterial molecules involved in pathogen infection and multiplication (Ge and Rikihisa, 2007; Huang et al, 2010; Lin et al, 2011; Troese et al, 2011; Mastronunzio et al, 2012; Oliva Chávez et al, 2015; Seidman et al, 2015; Villar et al, 2015b; Truchan et al, 2016). Definition of bacterial proteins involved in host-pathogen and vector-pathogen interactions may provide target antigens for the development of vaccines and therapeutics that interfere with pathogen host infection and transmission by ticks (Gomes-Solecki, 2014; de la Fuente and Contreras, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Uninfected and A. marginale (St. Maries strain)-infected RF/6A rhesus monkey choroidal endothelial cells (CRL-1780; American Type Culture Collection, Manassas, VA) and Ixodes scapularis embryonic ISE6 cells were cultured as described previously (8,42,43). Both host cell types infected with A. marginale were originally donated by Ulrike Munderloh (University of Minnesota, Minneapolis, MN).…”
Section: Methodsmentioning
confidence: 99%
“…Detection of the bacterium colocalizing with the endothelial cell marker von Willebrand factor in tissue sections from an experimentally inoculated calf indicates it is also capable of infecting endothelial cells in vivo and might serve as a reservoir for infection (6). Moreover, endothelial cell lines are useful for studying A. marginale infection in vitro, as they are the only mammalian cell types in which continuous cultivation of these microbes has been achieved (7,8). The immortalized tick cell line ISE6 is susceptible to A. marginale infection and supports its replication, making it a useful model for studying bacteriumtick cell interactions (9)(10)(11).…”
mentioning
confidence: 99%